A MIMO Robust Design of a PID for Refrigeration Systems based on Vapour Compression. Issue 4 (2018) - Tari, M.; Lanusse, P.
Abstract: In this paper, an original method for the design of PID Controller for MIMO application is presented. The proposed method is based on the CRONE MIMO approach which makes easier the design of MIMO robust controllers. The problem treated here is the control of a refrigeration system based on vapour compression in order to achieve high energy efficiency and to satisfy the cooling demand. Simulation results show the good control performance and robust stability for a wide set of operating points.